2021
DOI: 10.1002/cac2.12150
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world outcomes of ibrutinib therapy in Korean patients with relapsed or refractory mantle cell lymphoma: a multicenter, retrospective analysis

Abstract: Dear Editor, Despite the introduction of novel front-line therapies including rituximab plus high-dose cytarabine followed by consolidative autologous stem cell transplantation (ASCT) and salvage therapy with bendamustine, lenalidomide or bortezomib, mantle cell lymphoma (MCL) is still considered incurable and most patients experience relapse or refractory (RR) disease. Ibrutinib (Imbruvica R) is a firstin-class oral agent that mainly works by inhibiting Bruton's tyrosine kinase and is considered the standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 12 publications
5
19
2
Order By: Relevance
“…It is also worth mentioning that the median OS of 32 months is comparable to the one obtained in the clinical trial setting (26.7 months) and that the PFS of 20 months was superior, with similar median treatment exposure [ 10 ]. The median PFS and OS we observed are similar to the Korean cohorts published by Jeon et al (27 and 35 months) [ 13 ] and Yi et al (20.8 and NR) [ 16 ], with around 16 months of median treatment exposure, and compare favorably with those from the UK cohorts by Tucker et al (18.5 and 12 months) and McCulloch et al (17.8 and 23.9 months) with 10 months of median treatment exposure, and the Italian cohort (12.9 and 16 months) [ 11 ], with 6 months of median ibrutinib exposure.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…It is also worth mentioning that the median OS of 32 months is comparable to the one obtained in the clinical trial setting (26.7 months) and that the PFS of 20 months was superior, with similar median treatment exposure [ 10 ]. The median PFS and OS we observed are similar to the Korean cohorts published by Jeon et al (27 and 35 months) [ 13 ] and Yi et al (20.8 and NR) [ 16 ], with around 16 months of median treatment exposure, and compare favorably with those from the UK cohorts by Tucker et al (18.5 and 12 months) and McCulloch et al (17.8 and 23.9 months) with 10 months of median treatment exposure, and the Italian cohort (12.9 and 16 months) [ 11 ], with 6 months of median ibrutinib exposure.…”
Section: Discussionsupporting
confidence: 89%
“…Although not directly comparable to the clinical trial setting, the CR rate observed in the present study (38%) is higher than that observed in the pooled analysis (27%) [ 10 ] and similar observational studies (ranging from 15 to 27%) [ 11 , 13 , 14 ]. This is probably due to a larger proportion of patients in our study receiving 1–2 prior lines, which supports previous evidence showing better outcomes when ibrutinib is used in earlier lines of therapy [ 6 , 16 ] as well as the increased presence of poor prognostic factors with increasing lines of therapy [ 17 ]. Lower-risk disease (76% with low-intermediate sMIPI) and better performance in our patients (94% with an ECOG PS 0–1) compared to other real-world cohorts [ 11 , 13 , 15 ] may have also contributed to these observations.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations